Representasi Kekerasan Verbal Tokoh Perempuan Pada Film Serial Sianida: Kajian Analisis Wacana Kritis Norman Fairclough - Sri Rezeki, Tari (Kajian Linguistik dan Sastra, 2025)
This study aims to analyze how verbal violence against female characters is represented in the Cyanide serial film. The approach used is Norman Fairclough's critical discourse analysis which includes three main dimensions: text analysis (micro), discursive practice analysis (meso), and social practice analysis (macro). The main data in this study were obtained from the dialogue transcript of the Cyanide serial film, produced by MVP Entertainment, consisting of 12 episodes. The results of the study indicate that verbal violence against female characters in this film is represented through verbal violence against female characters Jenny, Dita, and Amelia who several times receive sentences with a threatening tone, ridicule, and verbal insults from male characters or those in power such as. "I'll kill you"! "Janda kembang sejakarta" "hey dog ​​woman". Verbal violence experienced by female characters does not cause direct physical injuries. However, the psychological and social impacts of this type of violence are no less serious than other forms of violence. This study is expected to contribute to similar studies, as well as being a reference for further similar research.